Experimental and numerical investigation of underwater composite repair with fibre reinforced polymers in corroded tubular offshore structural members under concentric and eccentric axial loads. (15th January 2021) - George, Jerin Mathew; Kimiaei, Mehrdad; Elchalakani, Mohamed; Fawzia, Sabrina
Highlights: Underwater composite repair under the combination of axial compression and bending loads. Experimental study looking into repaired in air and repaired underwater specimens. Comparison of the performance underwater composite repair with conventional in air repair. Finite element model to predict the performance of composite repair. Abstract: Repair of offshore steel structural members become essential due to the corrosive marine environment in which they exist. Structural repair using composite material has significant advantages in these cases than the conventional repair by welding or bolting steel sleeves. However, the composite repair technology with fibre reinforced polymers (FRP) is not very well established for their usage on load bearing offshore steel structural members either in underwater or above water conditions. The study had attempted to do a pilot experimental study on steel tubular members under the combination of axial compression and bending loads to address this gap in knowledge. The specimens were grouped into four categories: intact, corroded, repaired in air and repaired underwater. The repair scheme remained the same for in air and underwater repairs with one layer of glass and two layers of carbon fibre reinforced polymers, but with resin and repair methodology being different for both. The repaired specimens showed notable improvement in the ultimate strength from the corroded members to match the intact strength. Underwater repairs proved to be adequate to replicate the ultimate strength achieved by the conventional in air repairs. Investigations into parameters like load displacement behaviour, energy absorption, ductility and strain values also revealed that the underwater repair performed very similar to the conventional in air repair. A simplified Finite Element model simulating the repaired specimens was also presented in the paper which had predicted the experimental behaviour with great accuracy. In conclusion, the underwater and above water repair of structural steel tubular members using FRP composite materials seem a very viable solution for the corroded load bearing members in the offshore industry, however more detailed study on long term performance and cyclic behaviour of the composite repaired members is yet to be carried out.